Modelling Evaporation and Evapotranspiration under Temperature Change in Malaysia - Ali, Md. Hazrat; Shui, Lee Teang; Yan, Kwok Chee; Eloubaidy, Aziz F. (Universiti Putra Malaysia Press, 2000)
Temperature change has a direct effect on hydrology through its link with evapotranspiration. The potential impact of temperature change on the evapotranspiration is assessed; using a modelling approach based on a few physical weather measurements. Methods to estimate free-surface evaporation E and potential evapotranspiration ETp ' without any model calibration p~parameters, for monthly time series are presented. The model results are calculated by using observed average historic (1980-97) meteorological data and compared with USBR Class-A black pan evaporation data (1971-97) from the Muda Agricultural Development Authority, Malaysia. The long-term monthly averaged daily estimates of Ep for different months were compared with measured pan evaporation. Results of this simulation showed an accuracy of more than 95% with the observed pan evaporation data and thus, would be used for ET estimation. All the model equations containing temperature terms were set dependent of temperature. The correlation between mean monthly relative humidity and temperature was also made to investigate the sensitivity of ETp ' The ETp time series is perturbed by varying monthly temperature from 21"C to 41"C, with O.2"C increment to investigate the sensitivity of that series. Results from the perturbations showed that the temperature has significant effects on ET for each month. p